Effects of metallic and metal oxide nanoparticles in aquatic and terrestrial food chains. Biomarkers responses in invertebrates and bacteria. (7th February 2012) - Thiéry, A.; Jong, L. De; Issartel, J.; Moreau, X.; Saez, G.; Barthélémy, P.; Bestel, I.; Santaella, C.; Achouak, W.; Auffan, M.; Rose, J.; Bottero, J–Y.
Although the market of nanoparticles (NPs) is rapidly expanding, the environmental and health impact of manufactured NPs and nanomaterials is still poorly understood and predictable. Hence, several laboratories of the PACA region have unified their skills to address this issue with an interdisciplinary approach. We present an outline of the ecological impact of metallic and metal oxide NPs span from the surface atoms of NPs, to unicellular organisms, such as bacteria, and organism levels. On multicellular organisms, we focus on biomarkers reporting on stress, central nervous system endpoints and antioxidative balance assessment. On bacteria, which are key players in NPs transfer, we study not only the impact of NPs on cells, at the microbial community, cell and molecular level, but also the effect of cells on NPs. Our priority is through our collaborations, to surpass case–by–case studies and develop aquatic and terrestrial mesocosms, to get information at an integrative level on the trophic links and ecosystemic consequences of NPs.